Strategi Pengembangan Pariwisata Berbasis Masyarakat pada Objek Wisata Toronipa Kabupaten Konawe Provinsi Sulawesi Tenggara - Nasruddin Suyuti; Hartini . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
This article is the result of research on community-based tourism development strategy conducted on one of the tourism object, Toronipa beach, in Konawe Southeast Sulawesi Province. The problem of this research is to develop the potential of natural resources and human resources in the vicinity of the object Toronipa to support the development of community-based tourism in Konawe. The next problem is how to implement a strategy to support the development of tourism. To obtain field data, the study used two types of data; primary and secondary data. Methods of data collection using the method of observation and interviews, while the analysis of data using qualitative data analysis. The results indicate that a wide range of facilities available, such as a villa owned by the former Governor Ali Mazi, gazebo, public toilets, trash cans, guardhouse, and the lighting. While various types of businesses developed by the community in the form of a kiosk business, tire leasing, leasing mat, canoe and inflatable boats rentals. Community-based tourism development strategy in the tourism oject of Toronipa is community involvement in the development of the maximum attraction. Communities can perform a variety of good businesses that supply foods and beverages, various types of businesses as well as with regard to the comfort of tourists in the tour. While the strategy of community involvement in tourism development include planning development, attraction marketing, and management of a tourist attraction. Keywords: strategy development, tourism object, community.